Independent contractors vs employees - Joubert, Francois Jacques (Department of Commercial Law, 2023)
A question that often arises is whether a particular person is an employee or an independent contractor, and what the obligations of the employer in such circumstances are. The Fourth Schedule to the Income Tax Act requires any employer who pays any amount by way of remuneration to its employees to deduct pay-as-you-earn (PAYE) in accordance with the tables released by the South African Revenue Services (SARS).